Development of Differentiated Instruction Module Based on SICOMO (Searching Information Communication Modeling) on Membrane Transport Concept to Improve Critical Thinking - Zahranie, Laila Rahmah; Usman, Usman; Hendriyani, Mila Ermila; Promkaew, Suppamai (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2023)
This study aimed to develop a differentiated teaching module on the concept of membrane transport. This teaching module was expected to be an example of the development of differentiated teaching modules in Biology subjects. This research method was Research and Development which consists of several stages including potential and problems, data collection, product design, design validation, design revision. The development of teaching modules uses Canva, google sites, barcode websites, M.S word. The teaching module developed consists of three differentiated learning, namely process, content and product differentiation. The three learning differentiations were based on diagnostic analysis of student interests, learning profiles and student learning readiness. The teaching module also contains guidelines for differentiated learning activities on membrane transport material. The feasibility of the teaching module content obtained a score of 97.6 with a very good interpretation. The feasibility of teaching module users obtained a score of 95.19 with the interpretation of very feasible to use. The acquisition of this value indicates that the teaching module product developed is feasible to use and can be used as a guide in designing differentiated teaching modules in biology subjects. In developing teaching modules, it is better to use media that are more integrated with varied technologies such as quiz and teaching modules that can cover environmental differentiation as well.